Analisis Pengaruh Kualitas Pelayanan Publik terhadap Kepuasan Penumpang. Studi Kasus: Pelayanan Jasa Penumpang di Bandara Wiriadinata Tasikmalaya - Purwita, Wiwit; Bintoro, BP.Kusumo (Journal of Entrepreneurship, Management and Industry (JEMI), 2019)
Tasikmalaya is one of the advanced cities in terms of the economy, especially in terms of handicraft production, so that many people do business as craftsmen where their products are distributed to many cities or countries. To facilitate the shipment of goods, the development of air transportation is the most effective solution. However, it needs to be examined in terms of service satisfaction on passenger satisfaction so that it can be seen the effect of service quality and its variables on passenger satisfaction at Wiriadinata Airport, Tasikmalaya. The approach taken is the method of interview and quantitative research. A total of 100 respondents were involved in this study. The results of this study indicate that in this study is in accordance with the theory that service quality will be very dominant influence on passenger satisfaction and positive impact. The results of this study are also consistent with previous studies stating that service quality has an effect on passenger satisfaction. Because with good service in the form of Tangible, reliability, responsiveness, assurance and empathy will have a positive impact on passenger satisfaction at the airport Wiriadinata Tasikmalaya. In addition, it was revealed that overall service quality at Wiriadinata airport was quite good for passenger satisfaction.